PENGARUH AIR KELAPA HASIL FERMENTASI TERHADAP KUALITAS FISIK DAGING BROILER - Pramana, Weldi Adi; Septinova, Dian; Riyanti, Rr; Husni, Ali (JURUSAN PETERNAKAN, FAKULTAS PERTANIAN, UNIVERSITAS LAMPUNG, 2018)
The purpose of the research was determined the effect of using coconut water fermentation on physical quality of broiler meat.This research was conducted on March, 30th2018 at Production and Reproduction of Laboratory, Department of Animal Husbandry, Faculty of Agriculture University of Lampung.The materials of this research is used 20 pieces chest of broiler meat and coconut water fermentation. The experimental design used was Completely Randomized Design (RAL) with 5 treatments and 4 replications.Treatment given in this research is P0 (without coconut water fermentation, P1 (coconut water fermentation 25%), P2 (coconut water fermentation 50%),P3 (coconut water fermentation 75%),and P4 (coconut water fermentation 100%). The observed variables is value of pH, water holding capacity (WHC), and cooking loss.The data obtained in this study was analyzed by using variance analysis (ANOVA), the results of which have significant effect on continued test using Least Significance Different (BNT). The results showed that use coconut water fermentationdid not significant effect (P>0,05) to WHC and cooking loss of broiler meat, but use coconut water fermentation at concentration 100% have significant effect on value of pH of broiler meat. The best value of broiler meat pH that is on treatment of P4 (coconut water fermentation 100%) with average value that is 5,599. Key words: Coconut water fermentation, Physical quality of broiler meat, and Broiler meat.